Bridging Cultural Identity and Digital Transformation in EFL Classrooms: A Sociocultural Perspective from Indonesia - Nurhaliza, Salsabila; Sofendi, Sofendi; Mirizon, Soni (FKIP Universitas Lampung, 2025)
Bridging Cultural Identity and Digital Transformation in EFL Classrooms: A Sociocultural Perspective from Indonesia. Small and Secondary Cities in Indonesia face specific challenges when implementing digital transformation in English Language Learning (ELL). This research investigates such challenges in Palembang, South Sumatra, Indonesia, where technology and local (culture-based) values are not well integrated into English language teaching. Objectives: This study aimed to explore the availability and use of digital technologies, the infusion of local culture into teaching-inspired materials and practices, and the challenges and opportunities faced by teachers in developing culturally responsive, digitally based English instruction across varied school types in Palembang. Method: Employing a descriptive qualitative design, data were obtained through semi-structured interviews conducted with five English teachers from urban public, suburban, private, semi-rural, and madrasah schools. The data were analyzed thematically. Findings: Three themes emerged from the interviews conducted with the participants. Inequality in access to and use of digital technology between urban and semi-rural schools is considerable due to infrastructural challenges that discourage effective pedagogical practices. There is little representation of Palembang's local culture in the English-language instructional materials developed for students, despite teachers believing it could serve as a valuable component of the educational process. Conclusion: This study shows that meaningful digital transformation in English language education cannot rely solely on technology. It requires a coordinated approach that strengthens both technological infrastructure and culturally relevant pedagogy. For digital integration to truly benefit students, schools need system-level support: curriculum reforms that allow space for regional content, ongoing professional development that blends digital skills with cultural pedagogy, and fair resource distribution that prioritizes underserved schools. Without these combined efforts, digital initiatives risk deepening rather than reducing existing educational inequalities. Keywords: culturally responsive pedagogy, digital divide, teacher agency, english language learning.